Sampling and survey design of the Bangladesh long-term impact study. - Hassan, Md. Zahidul; Quabili, Wahid; Zobair, Mohammad; Baulch, Bob; Quisumbing, Agnes R. (Journal of Development Effectiveness, 2011)
This appendix describes the sampling and survey design of the longitudinal study on which the papers in this collection are based. Special attention is paid to the design of the treatment and comparison groups, tracking of households, and the integrated nature of the quantitative and qualitative phases in the 2006-2007 re-survey.